PROSEDUR PEMBERIAN KREDIT PEMILIKAN RUMAH (KPR) DI PT BANK TABUNGAN NEGARA (PERSERO) TBK KANTOR CABANG PEMBANTU MEDAN JOHOR - Gunawan, Sarah Angelica; Asmalidar (Jurnal Budgeting, 2024)
This research is entitled "Procedure for Providing Home Ownership Credit (KPR) at PT Bank Tabungan Negara (Persero) Tbk Medan Johor Sub-Branch Office." The aim of this research is to find out the procedure for granting subsidized home ownership credit and to find out whether the procedure for granting Home Ownership Credit (KPR) at PT Bank Tabungan Negara (Persero) Tbk Medan Johor Sub-Branch Office is in accordance with Kasmir theory (2014). Data collection techniques were carried out by interviews. The data processing method used is a descriptive method which is then compared with existing theory. The research results show that the procedure for granting Home Ownership Credit at PT Bank Tabungan Negara (Persero) Tbk Medan Johor Sub-Branch Office is not in accordance with the Kasmir theory.